Development of Application for Augmented Reality for Three States of Matter - Mohd Tarmizi , Fatin Amirah; Yasak, Zurina (Research and Innovation in Technical and Vocational Education and Training, 2022)
The rapid development of technology and information has a powerful impact on education. Among the technologies that have been used is the use of Augmented Reality which can help improve the effectiveness of the delivery of learning content in the classroom such as facilitating students learning the topic of matter in chemistry form four by looking at the structure of particles in three dimensions and integrating them into the real world. The topic of the three states of matter is difficult for students to understand, especially for students with chemophobia and students who are less interested in learning about this topic. Therefore, this study is to design and develop Augmented Reality applications for the state of matter molecules (solid, liquid and gas) and to evaluate and test the functionality of the application. In this study, the researcher applied the product development method using the ADDIE design model which has five phases that is the analysis phase, design phase, development phase, implementation phase and evaluation phase. The research instrument used by the researcher is a questionnaire and expert verification form distributed to two multimedia experts and teachers who teach chemistry subjects. The results show that all the experts have responded positively to the development of this application in terms of content design, interaction design and interface design. The application is also well developed and has achieved the objectives of the study. This study can be further expanded by developing this application for other topics and using the iOS platform as well as uploading to the Apps Store or Play Store so that it can be exposed and used by anyone.